Recommendation on Design, Execution, and Reporting of Animal Atherosclerosis Studies: A Scientific Statement From the American Heart Association. Issue 9 (September 2017) - Daugherty, Alan; Tall, Alan R.; Daemen, Mat J.A.P.; Falk, Erling; Fisher, Edward A.; García-Cardeña, Guillermo; Lusis, Aldons J.; Owens, A. Phillip; Rosenfeld, Michael E.; Virmani, Renu
Abstract : Animal studies are a foundation for defining mechanisms of atherosclerosis and potential targets of drugs to prevent lesion development or reverse the disease. In the current literature, it is common to see contradictions of outcomes in animal studies from different research groups, leading to the paucity of extrapolations of experimental findings into understanding the human disease. The purpose of this statement is to provide guidelines for development and execution of experimental design and interpretation in animal studies. Recommendations include the following: (1) animal model selection, with commentary on the fidelity of mimicking facets of the human disease; (2) experimental design and its impact on the interpretation of data; and (3) standard methods to enhance accuracy of measurements and characterization of atherosclerotic lesions.